In-Silico Studies of Compounds Derived from Brucea javanica (L.) Merr. as Potential Inhibitors of Influenza A Neuraminidase H5N1 - Nuwarda, Rina Fajri (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
The H5N1 bird flu virus continues to be endemic in Indonesia, posing continued threats to the poultry farming industry and public health. Classified as an influenza type A virus, the avian influenza virus is a member of the Orthomyxoviridae family. Type A influenza virus is the most lethal strain and frequently evolves resistance. The exploration of novel neuraminidase (NA) inhibitors is imperative due to the development of resistance by the H5N1 virus to NA drugs. Brucea javanica extract inhibits the activity of the H5N1 NA enzyme, according to previous research. Using the molecular docking technique, this study sought to ascertain the in-silico activity of the B. javanica compound in relation to H5N1 NA. By utilizing molecular docking simulation, we conducted the in-silico study and predicted the toxicity and pharmacokinetic profile of compounds, in addition to their drug-likeness according to Lipinski's Rule of Five. The result showed that Bruceantinol had a free binding energy of -8.93 kcal/mol, an inhibition constant of 0.28 M, and interactions with six important amino acid residues. The HIA and CaCo-2 values were 47.935% and 19.871%, respectively, whereas the PPB and BBB values were 39.591% and 0.049%. Neither is this substance carcinogenic nor mutagenic. Low binding energy and the most favored interaction with H5N1 NA were observed for Bruceantinol. Thus, Bruceantinol exhibits potential as a prospective NA inhibitor.